Numerical Investigation of the Effect of Tower Dam and Rotor Misalignment on Performance and Loads of a Large Wind Turbine in the Atmospheric Boundary Layer - Gilberto Santo; Mathijs Peeters; Wim Van Paepegem; Joris Degroote (Energies, 2019)
A modern horizontal axis wind turbine was simulated by means of computational fluid dynamics (CFD) simulations. The analyzed machine has a diameter of 100 m and is immersed in the atmospheric boundary layer (ABL). The velocity and turbulence stratification of the ABL is correctly preserved along the domain by the adoption of modified wall functions. An overset technique is employed to handle the rotation of the turbine rotor throughout the operation of the machine. The ABL induces periodically oscillating loads and generated torque on the rotor blades. Several configurations are analyzed. First, the results of a rotor-only simulation are compared to the ones obtained from the simulation of the full machine in order to evaluate the effect of the supporting structures on the produced torque and on the loads acting on the blades. Then, a tilt angle is introduced on the analyzed rotor and its effect on the oscillating loads of each blade is highlighted by comparing the results to the untilted configuration. Lastly, a yaw misalignment is also introduced and the results are compared to the unyawed configuration.